2022
DOI: 10.1021/acs.jpclett.2c02035
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Correlated High-Resolution Spectra and the Structure of Benzene

Abstract: Mass-correlated rotational alignment spectroscopy resolved the rotational Raman spectra for 5 benzene isotopologues with unprecedented resolution. 13-C isotopologues were characterized at natural abundance. Fitted rotational constants allowed the analysis of effective and equilibrium bond lengths for benzene with sub-mÅ uncertainties. We found that previously reported experimental structures were wrong by multiple mÅ, due to unrecognized H/D isotope effects. Our results also refute recent experimental and theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The 2D-COS Raman spectra analysis summary is depicted in Figure A5,A6 for self-healable (interchain face-centered/unperturbed Sty) and non-self-healable (off-centered/intrachain face-centered Sty) copolymers. Although even uninterpreted styrene on p­(Sty/ n BA) is expected to have asymmetry represented by splitting the C–C breathing mode, recent studies have shown that even free benzene rings exhibit no even potential energy surfaces due to the displacement of H atoms along the in-plane symmetric and out-of-plane bending modes. Although the presence of the 997, 1000, and 1003 cm –1 bands may be attributed to off-centered/T-shaped, unperturbed, and face-centered Sty–Sty interactions, the proximity of n BA side groups containing polar CO and C–O–C moieties may also play a role.…”
Section: Resultsmentioning
confidence: 99%
“…The 2D-COS Raman spectra analysis summary is depicted in Figure A5,A6 for self-healable (interchain face-centered/unperturbed Sty) and non-self-healable (off-centered/intrachain face-centered Sty) copolymers. Although even uninterpreted styrene on p­(Sty/ n BA) is expected to have asymmetry represented by splitting the C–C breathing mode, recent studies have shown that even free benzene rings exhibit no even potential energy surfaces due to the displacement of H atoms along the in-plane symmetric and out-of-plane bending modes. Although the presence of the 997, 1000, and 1003 cm –1 bands may be attributed to off-centered/T-shaped, unperturbed, and face-centered Sty–Sty interactions, the proximity of n BA side groups containing polar CO and C–O–C moieties may also play a role.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy is an alternative to those based on the electric dipole transition. Time-domain spectroscopy combined with a sensitive detection method such as ionization would be effective for high-resolution (rotational) Raman spectroscopy of molecular complexes, for which preparation of high concentration samples is difficult. We note that time-domain rotational spectroscopy (rotational coherence spectroscopy) was pioneered by Felker et al In the early stage of the development of the time-domain method, rotational wave packet dynamics were initiated by vibronic transitions. Owing to advancements in ultrashort intense laser techniques, extensive research has been conducted to generate rotational wave packets of molecules and molecular complexes in the electronic ground state via impulsive Raman processes and to subsequently track their spatio-temporal dynamics by measuring their ionization efficiency for linearly polarized intense pulses or orientation distribution through Coulomb explosion imaging in a pump–probe manner. , ,,,, In these studies, Fourier transformation of time-dependent observables yields pure rotational spectra, wherein peak frequencies correspond to energy differences between two eigenstates contributing a wave packet. ,, The frequency resolution of time-domain spectroscopy is limited by the longest pump–probe delay time. Schultz et al conducted a microseconds pump–probe experiment, and achieved MHz frequency resolution, opening up possibilities to investigate larger, more complex molecular systems with time-domain rotational Raman spectroscopy. ,, …”
Section: Introductionmentioning
confidence: 99%
“…5−7,9−14,18,19,27,29−35 In these studies, Fourier transformation of time-dependent observables yields pure rotational spectra, wherein peak frequencies correspond to energy differences between two eigenstates contributing a wave packet. [5][6][7][8][9][10][11][12][13][14]18,20 The frequency resolution of time-domain spectroscopy is limited by the longest pump−probe delay time. Schultz et al conducted a microseconds pump−probe experiment, and achieved MHz frequency resolution, opening up possibilities to investigate larger, more complex molecular systems with time-domain rotational Raman spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…More recently, Heo and coworkers also tackled this issue. 6 They analyzed the H/D isotope effects using masscorrelated rotational alignment spectroscopy and density functional theory. However, different from our previous findings, 2,4 they insisted that the H/D isotope effects for benzene were similar to those observed for the other small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…They analyzed, in terms of local modes, the stretching and bending potentials of the C–H­(D) bond in benzene and demonstrated that the projected C–H bond length in C 6 H 6 benzene r 0,C–H proj and the projected C–D bond length in C 6 D 6 benzene r 0,C–D proj were almost the same, that is, 1.0815 and 1.0819 Å, respectively, although the vibrationally averaged bond length r 0,C–H for C 6 H 6 (1.0911 Å) is longer than r 0,C–D for C 6 D 6 (1.0888 Å). More recently, Heo and coworkers also tackled this issue . They analyzed the H/D isotope effects using mass-correlated rotational alignment spectroscopy and density functional theory.…”
Section: Introductionmentioning
confidence: 99%